THE USE OF ARTIFICIAL INTELLIGENCE IN THE PREPARATION OF ENGLISH TEACHING MATERIALS IN VOCATIONAL SCHOOLS - Meriyan Elza; Resa Yulita; Hudia (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
Artificial intelligence (AI) can be used by teachers to create specific English teaching materials for various fields in vocational high schools. This research aimed at finding out how English teachers in vocational high schools used AI in creating teaching materials. This research was conducted in 9 vocational high schools in Payakumbuh City, both public and private, where the research subjects were English teachers. Data were collected by distributing questionnaires and conducting interviews. The data were then classified based on the categories of platform for each reading, writing, listening, and speaking skill, as well as teachers’ responses to the use of AI. The research results showed that English teachers at the vocational high schools in Payakumbuh City barely used AI, they were still at the stage of using a few narrow AI platforms a translation platform or application. Teachers were not familiar with various platforms for the other four skills in English. On the other side, even though they had not used AI, but 72.2% of teachers agreed that AI is an important technology and can save their time in preparing up-to-date English teaching materials. It is hoped that this research will be able to motivate English teachers to recognize the features offered by AI to prepare English teaching materials that are authentic and field-specific in vocational schools.